Melatonin-Mediated Suppression of mtROS-JNK-FOXO1 Pathway Alleviates Hypoxia-Induced Apoptosis in Porcine Granulosa Cells - Xuan Zhang; Dingding Zhang; Hongmin Li; Zhaojun Liu; Yatong Yang; Jiameng Li; Lishiyuan Tang; Jingli Tao; Honglin Liu; Ming Shen (MDPI AG, 2023)
Numerous studies have established that the hypoxic conditions within ovarian follicles induce apoptosis in granulosa cells (GCs), a pivotal hallmark of follicular atresia. Melatonin (N-acetyl-5-methoxytryptamine, MT), a versatile antioxidant naturally present in follicular fluid, acts as a safeguard for maintaining GCs' survival during stress exposure. In this study, we unveil an innovative protective mechanism of melatonin against hypoxia-triggered GC apoptosis by selectively inhibiting mitochondrial ROS (mtROS) generation. Specifically, under hypoxic conditions, a gradual accumulation of mitochondrial ROS occurred, consequently activating the JNK-FOXO1 pathway, and driving GCs toward apoptosis. The blocking of JNK or FOXO1 diminished hypoxia-induced GC apoptosis, but this effect was nullified in the presence of GSH, indicating that mtROS instigates apoptosis through the JNK-FOXO1 pathway. Consistent with this, hypoxic GCs treated with melatonin exhibited decreased levels of mtROS, reduced JNK-FOXO1 activation, and mitigated apoptosis. However, the protective capabilities of melatonin were attenuated upon inhibiting its receptor MTNR1B, accompanied by the decreased expression of antioxidant genes. Notably, SOD2, a key mitochondrial antioxidant gene modulated by the melatonin-MTNR1B axis, effectively inhibited the activation of mtROS-JNK-FOXO1 and subsequent apoptosis, whereas SOD2 knockdown abrogated the protective role of melatonin in hypoxic GCs. In conclusion, our study elucidates that melatonin, through MTNR1B activation, fosters SOD2 expression, effectively quelling mtROS-JNK-FOXO1-mediated apoptosis in follicular GCs under hypoxic stress.